Boundedness for the Commutator of Fractional Integral on Generalized Morrey Space in Nonhomogeneous Space (Analysis in Theory and Applications, 2018)
In this paper, we will establish the boundedness of the commutator generated by fractional integral operator and $RBMO(μ)$ function on generalized Morrey space in the non-homogeneous space.
Keywords: fractional integral operator; commutator; generalized Morrey space; $RBMO(μ)$.